Activité antimicrobienne de Streptomyces sp. S20 isolée à partir des rives du barrage Ain Dalia, Souk - Ahras - BOUGHANI Ouafa; BOULARES Meriem (My University, 2017)
Streptomyces sp. S20, new species, capable of inhibiting the growth of four microorganisms Pathogens: Citrobacter freundii 1108, Escherichia coli 1094, Pseudomonas aeruginosa 525 and Candida albicans. Extraction and partial purification of components through chromatography techniques on thin layer showed that the crude butanolic extract of Streptomyces sp. S20 against Citrobacter freundii 1108, indicates that it contains two active compounds 20A and 20B. This suggests that we are in the presence of either a single antibiotic or a complex of antibiotics with different chemical structures. And for the Ethyl acetate extract, it contains three active compounds 20C, 20E and 20F. Even for n-hexane contains three active compounds 20G, 20H and 20I. However, the acetic acid extract contains two active compounds 20J and 20K. whichever we are in the presence of either a single antifungal, or a complex of antifungals. The analysis of the crude extract 20F by UV-visible spectrophotometry showed that it contains substances of a polyene nature, which are characterized by the presence of a peak characteristic of pentaenes. Purification by HPLC showed that this fraction presents a well-developed peak (very fine) with a retention time: 20-F1 (Tr =1.642 min). The study of the antibacterial activity of this fraction showed that it is active against Citrobacter freundii. ----------------------------------------------------------------------------------- Streptomyces sp. S20، نوع جديد، قادر على منع نمو أربعة كائنات حية دقيقة مسببات للأمراض: Citrobacter freundii 1108، Escherichia coli 1094، Pseudomonas aeruginosa 525 و Candida albicans. أظهر الاستخراج والتنقية الجزئية للمكونات من خلال تقنيات التحليل الكروماتوغرافي على طبقة رقيقة أظهرت أن المستخلص البيوتانولي الخام لبكتيريا Streptomyces sp. S20 ضد Citrobacter freundii 1108، يشير إلى أنه يحتوي على مركبين نشطين 20A و20B. مما يشير إلى امكانية وجود مضادًا حيويًا واحدًا أو مجموعة معقدة من المضادات الحيوية ذات تركيبات كيميائية مختلفة. أما بالنسبة لمستخرج الجزئي خلات الإيثيل فيحتوي على ثلاثة مركبات نشطة هي 20C و20E و20F. حتى بالنسبة لمستخرج الجزئي الهكسان n يحتوي على ثلاثة مركبات نشطة 20G و20H و20I. ومع ذلك، يحتوي مستخرج حمض الأسيتيك على مركبين نشطين 20J و20K. مما يوحي الى وجود مضاد فطرٌات واحد أو مركب مضاد للفطريات. وأظهر تحليل المستخرج الخام 20F بواسطة القياس الطيفي للأشعة فوق البنفسجية أنه يحتوي على مواد ذات طبيعة بوليينية والتي تتميز بوجود خاصية ذروة المتميزة ل pentanes. وأظهرت التنقية بواسطة HPLC أن هذا الجزئي يمثل ذروة متطورة (ناعم جدا)مع وقت الاحتفاظ ل 20-F1 (Tr = 1.642) دقيقة. أظهرت دراسة النشاط المضاد للبكتيريا أن هذا الجزئي نشط على Citrobacter freundii. ---------------------------------------------------------------------------------------------- Streptomyces sp. S20, nouvelle espèce, capable d’inhiber la croissance de quatre micro- organismes Pathogènes : Citrobacter freundii 1108, Escherichia coli 1094, Pseudomonas aeruginosa 525 et Candida albicans. L’extraction et purification partielle des composants à travers des techniques de chromatographie sur couche mince a montré que l’extrait brute butanolique de Streptomyces sp. S20 contre Citrobacter freundii 1108, indique qu’il contient deux composés actifs 20A et 20B. Ce qui suggère que l’on est en présence soit d’un seul antibiotique, soit d’un complexe d’antibiotiques à structure chimique différente. Et pour l’extrait Ethyle acétate, il contient trois composés actifs 20C, 20E et 20F. Même pour l’ n- hexane contient trois composés actifs 20G, 20H et 20I. Cependant l’extrait acide acétique contient deux composés actifs 20J, et 20K. ce qui que l’on est en présence soit d’un seul antifongique, soit d’un complexe d’antifongiques. L’analyse de l’extrait brut 20F par spectrophotométrie UV- visible a montré qu’il contient de substances de nature polyénique, les quelles sont caractérisées par la présence d’un pic caractéristique des pentaènes. La purification par CLHP a montré que cette fraction présente un pic bien développé (très fin) avec un temps de rétention : 20-F1(Tr =1.642 min). L’étude de l’activité antibactérienne de cette fraction a montré qu’elle est active sur Citrobacter freundii.